2010
DOI: 10.1200/jco.2010.30.7702
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Esophageal Cancer Staged With [18F]Fluorodeoxyglucose Positron Emission Tomography (FDG-PET): Can Postchemoradiotherapy FDG-PET Predict the Utility of Resection?

Abstract: Purpose To determine whether [18F]fluorodeoxyglucose positron emission tomography (FDG-PET) can delineate patients with esophageal cancer who may not benefit from esophagectomy after chemoradiotherapy. Patients and Methods We reviewed records of 163 patients with histologically confirmed stage I to IVA esophageal cancer receiving chemoradiotherapy with or without resection with curative intent. All patients received surgical evaluation. Initial and postchemoradiotherapy FDG-PET scans and prognostic/treatment v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 50 publications
1
78
0
1
Order By: Relevance
“…18 F-FDG PET scans were performed and analyzed pre-and post-CRT. In a study undertaken by Monjazeb et al (16), for patients treated with definitive CRT, the median survival time and the 2-year overall survival (OS) rate for the patients achieving complete response was 38 months, and 71% vs. 11 months and 11% for those patients who had not achieved a complete response. Multivariate analysis indicated that PET complete response is the strongest independent prognostic factor for esophageal cancer [survival hazard ratio (HR), 9.82; P<0.01; local failure HR, 14.13; P<0.01].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FDG PET scans were performed and analyzed pre-and post-CRT. In a study undertaken by Monjazeb et al (16), for patients treated with definitive CRT, the median survival time and the 2-year overall survival (OS) rate for the patients achieving complete response was 38 months, and 71% vs. 11 months and 11% for those patients who had not achieved a complete response. Multivariate analysis indicated that PET complete response is the strongest independent prognostic factor for esophageal cancer [survival hazard ratio (HR), 9.82; P<0.01; local failure HR, 14.13; P<0.01].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that 18 F-FDG PET is a non-invasive method for monitoring pathological response and prognosis for carcinomas of the esophagus during or following neoadjuvant CRT (4-8). Monjazeb et al (16) reviewed 163 patients with esophageal cancer receiving neoadjuvant CRT with or without resection. 18 F-FDG PET scans were performed and analyzed pre-and post-CRT.…”
Section: Discussionmentioning
confidence: 99%
“…251,252 PET scan has also been shown to predict histopathologic complete response and outcome after definitive chemoradiation or preoperative chemoradiation in patients with locally advanced esophageal cancer. [253][254][255][256][257][258] However, other studies have shown conflicting results. [259][260][261][262][263][264] Swisher et al 254 also showed that a postchemoradiation 18-fluorodeoxyglucose (FDG) uptake value of 4 or less was found to be the only preoperative factor to correlate with decreased survival.…”
Section: Response Assessment and Additional Treatmentmentioning
confidence: 99%
“…The first 6 trials (Urba [55], Walsh [56], EORTC [57], Australasian [58], Korea [32], and CALGB 9781 [59]) had limited patient numbers, heterogeneous treatment regimens, and in some the dose of radiation was insufficient based. With the publication of the CROSS trial the standard of care for patients with locally advanced but medically resectable adenocarcinoma of the esophagus is now preoperative chemoradiation.…”
Section: Neoadjuvant Therapy Preoperative Chemoradiationmentioning
confidence: 99%
“…There are seven randomized trials comparing preoperative combined modality therapy with surgery alone in patients with clinically resectable disease, the most recent being the CROSS trial [32, [55][56][57][58][59][60].…”
Section: Neoadjuvant Therapy Preoperative Chemoradiationmentioning
confidence: 99%